2011
DOI: 10.1364/boe.2.000996
|View full text |Cite
|
Sign up to set email alerts
|

Photoplethysmographic imaging of high spatial resolution

Abstract: We present a new method of formation photoplethysmographic images with high spatial resolution from video recordings of a living body in the reflection geometry. The method (patent pending) is based on lock-in amplification of every pixel of the recorded video frames. A reference function required for synchronous detection of cardiovascular pulse waves is formed from the same frames. The method is featured by ability to visualize dynamic changes in cardiovascular pulse wave during the cardiac (or respiratory) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
133
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(135 citation statements)
references
References 10 publications
1
133
0
1
Order By: Relevance
“…rPPG-images are the outcome of a two-step approach, where signals are first extracted from each collocated skin site, recorded by a video camera and then correlated with a Hilberttransformed reference function for the remote-PPG signal [3]. Such reference is the same for all sensor locations.…”
Section: Bpi Pbvmentioning
confidence: 99%
See 2 more Smart Citations
“…rPPG-images are the outcome of a two-step approach, where signals are first extracted from each collocated skin site, recorded by a video camera and then correlated with a Hilberttransformed reference function for the remote-PPG signal [3]. Such reference is the same for all sensor locations.…”
Section: Bpi Pbvmentioning
confidence: 99%
“…Remote-PPG (rPPG) imaging was first proposed, in visible light, by Verkruysse et al [2] to describe the effect of blood coagulation on the amplitude and phase delay of PPG signals in skin, while Kamshilin et al [3] has subsequently shown enhanced resolution by computing rPPG-images as a similarity metricthe complex inner-product using the Hilbert operator-between a reference PPG-function and an array of PPG-virtual sensors spanning a given skin region of interest (RoI). Camera-based rPPG imagers have been proposed to improve remote pulse rate extraction and to detect medical conditions in the skin tissue [2][3][4]. However, exploring the potential of this developing technique requires a better understanding of the spatially varying phase and pulsating strength that is inherent to mapping PPG signals using the complex inner-product.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A synchronous detection approach was used to distinguish weak signal in a strong random noise background. This method was previously proposed by [15] , where a reference function formed from a large area was applied on spatially distributed small ROIs. This paper investigates how the area size used to establish a reference signal influences synchronous detection on various cites of arbitrary size.…”
mentioning
confidence: 99%
“…[37][38][39][40][41] In the last 10 years, pulse oximetry has undergone significant development 42 in noncontact monitoring, [43][44][45] in imaging, [46][47][48] and finally in incorporating diffuse imaging and backscattering in remote systems. [49][50][51] An alive human is a source of much noise upon breathing, talking, beating of the heart, and physiological and psychological states, in addition to the actual illness that is being assessed. Several established experimental techniques may be used to ameliorate the effects of temporal noise.…”
Section: Introductionmentioning
confidence: 99%